36.3k views
5 votes
Find the derivative for the function.

Find the derivative for the function.-example-1
User Rubmz
by
5.4k points

1 Answer

6 votes

The rule for deriving a multiplication is


(f(x)\cdot g(x))' = f'(x)g(x)+f(x)g'(x)

Also, we can forget about the factor 4 for now, since we have


(4f(x)\cdot g(x))' = 4(f'(x)g(x)+f(x)g'(x))

So, we will just multiply everything by 4 at the end. Our functions are


f(x) = (x^7-9)^(12),\quad g(x) = (4x+8)^(11)

For both derivatives we will use the rule


(f(x)^n)' = n\cdot f(x)^(n-1)\cdot f'(x)

So, we have


f'(x) = 12\cdot(x^7-9)^(11)\cdot 7x^6,\quad g'(x) = 11\cdot(4x+8)^(10)\cdot 4

We can simplify those expression a little bit:


f'(x) = 84x^6(x^7-9)^(11),\quad g'(x) = 44(4x+8)^(10)

The formula
f'(x)g(x)+f(x)g'(x) thus becomes


84x^6(x^7-9)^(11)\cdot (4x+8)^(11) + (x^7-9)^(12) \cdot 44(4x+8)^(10)

And so the final answer is


4(84x^6(x^7-9)^(11)\cdot (4x+8)^(11) + (x^7-9)^(12) \cdot 44(4x+8)^(10))

If you simplify this expression by factoring common terms, you will see that the correct answer is the first one.

User Shay Altman
by
5.1k points